Adrenomedullin attenuates ventilator-induced lung injury in mice. Issue 12 (22nd October 2010) - Müller, Holger Christian; Witzenrath, Martin; Tschernig, Thomas; Gutbier, Birgitt; Hippenstiel, Stefan; Santel, Ansgar; Suttorp, Norbert; Rosseau, Simone
Abstract : Background: Mechanical ventilation (MV) is a life-saving intervention in acute respiratory failure without any alternative. However, even protective ventilation strategies applying minimal mechanical stress may evoke ventilator-induced lung injury (VILI). Adjuvant pharmacological strategies in addition to lung-protective ventilation to attenuate VILI are lacking. Adrenomedullin exhibited endothelial barrier-stabilising properties in vitro and in vivo. Methods: In untreated mice (female C57/Bl6 mice, 11–15 weeks old) and animals treated with adrenomedullin, lung permeability, local and systemic inflammation and markers of distal organ function were assessed following 2 or 6 h of mechanical ventilation with 100% oxygen and protective or moderately injurious ventilator settings, respectively. Results: Adrenomedullin dramatically reduced lung permeability in VILI in mice, leading to improved oxygenation. Adrenomedullin treatment reduced myosin light chain phosphorylation, attenuated the accumulation of leucocytes in the lung and prevented the increase in lactate and creatinine levels in mice ventilated with high tidal volumes. Moreover, adrenomedullin protected against VILI even when treatment was initiated 2 h after the beginning of mechanical ventilation in a 6 h VILI mouse model. Conclusion: Adjuvant treatment with adrenomedullin may be a promising new pharmacological approach to attenuate VILI.